Description of the Level of Anxiety in the Community Villages in Facing the Covid-19 Pandemic in the Village of Selagedang Kec. Cibeber Cianjur Regency in 2021 - Fanny Hidayat; Achmad Zainuri; Yulianti Hayati; Kurnia Afriyanti (International Journal of Scientific Multidisciplinary Research, 2023)
The 2020 COVID-19 Positive Rate reported by the World Health Organization (WHO) updated data as of May 10 2020 that 215 countries have been confirmed infected with COVID-19 including the State of Indonesia, with a positive number of confirmed COVID-19 cases in the World 3884434 and the number Confirmed mortality in the world is 272859 people, with data estimates continuing to grow. Based on the updated PIKOBAR data on May 10, 2020, the number of confirmed cases in Indonesia is 14032, with a confirmed recovery rate of 2698, with a confirmed mortality rate of 973, with estimates that the data will continue to grow. COVID-19 causes anxiety due to changing lifestyles and limited space for movement due to restrictions made to prevent transmission of COVID-19